PENGARUH CITRA PERUSAHAAN DAN RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN PADA GRAND HAWAII HOTEL PEKANBARU - Roberto "; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Corporate image is a set of beliefs and impressions that consumers have of a company. A good and positive corporate image is a competitive advantage in realizing the company's goals.Relationship Marketing is the process to produce, defend, And advance relationship at strong with a customer and stakeholder another. Loyal customers can grow from the customer’S willingness to buy back because of a commitment to a brand, product or service or company.The researsch was conducted at Grand Hawaii Hotel Pekanbaru located at Gatot Subroto street no. 8 Pekanbaru. The problem in this research is the number of fluctuating room service sales at Grand Hawaii Hotel Pekanbaru, in the last 5 years that did not reach the target. This sample has taken about 100 responden of population which is calculating using slovin formula.The porpuse of this study is to determine hte effect of relationship marketing and corporate image of customer loyalty at Grand Hawaii Hotel Pekanbaru. In this research the mothod used is descriptive and quantitative with SPSS program. The sample of this study was taken as many as 100 responders from the population calculated using the slovin formula. Data obtained from the results of the questionnaire and then tested with statistics through the program SPSS 21.From the results of data analysis that includes the validity test, reliability, simple linear regression and multiple linear regression. Test condusted show that corporate image have a positive and significand impact on cumtomer loyalty, and relationship marketing have a positive and significant impact on customer loyalty at Grand Hawaii Hotel Pekanbaru.Keywords : Corporate Image, Relationship Marketing and Customer Loyalty